Income Inequality Convergence Across EU Regions - Francesco Savoia (Luxembourg Income Study (LIS), 2020)
Economic inequality has increased in many EU countries in the last decades. Yet, efforts assessing economic disparities across the EU regions mostly concentrate on convergence in average per capita incomes, offering little evidence on how regional income is distributed. Using data from Luxembourg Income Study (LIS) over the 1989-2013 period, this study contributes to fill this gap, focussing on whether there has been convergence of income inequality among EU regions, and on to what extent regional initial conditions and the Cohesion Policy funds affect the convergence process. Cross-section and panel convergence regressions, after a number of robustness checks, offer three findings. First, NUTS2 regions are converging to higher level of income inequality, so becoming equally more unequal. Second, this process is significantly faster when regions share similar structural characteristics, such as similar levels of governance quality. Finally, in regions eligible for Cohesion Policy funds the pace of inequality convergence has been significantly faster, suggesting therefore that they may be driving the convergence process.
Keywords: O15; O52; D31; P48; 330; Inequality; Income distribution; Convergence; Cohesion Policy; European Union